Analisa Penelitian Manajemen Proyek Yang Diterapkan Usaha “Tatakanku” - Wendy Winata; Erwin Erwin; Steven Steven; Andrean Andrean; Hendri Vinchen; Yuswardi Yuswardi (STIE AMKOP, 2023)
Laporan ini membahas mengenai usaha